INTEGRASI EPISTEMOLOGI BARAT–ISLAM SEBAGAI DASAR PENGEMBANGAN PEMBELAJARAN PAI PADA KURIKULUM MERDEK - Fitri Anggraini, fitri; Munir Munir; Ismail Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the integration of Western-Islamic epistemology as a foundation for developing Islamic Religious Education (PAI) learning in Indonesia's Kurikulum Merdeka. The problematic dichotomy of knowledge and fragmentation of PAI learning necessitates epistemological reconstruction that bridges Western rationalism-empiricism with Islamic bayani, burhani, and irfani paradigms. Employing qualitative methods through library research and content analysis, this study identifies epistemological integration constructs that harmonize revelation, reason, spiritual intuition, and empirical experience in a holistic knowledge system. Findings indicate that the transintegrative paradigm can be operationalized through circular-thematic approaches, value-based contextual learning, and Quran-science integration responsive to the flexibility and differentiation principles of Kurikulum Merdeka. Implementation strategies include adaptive curriculum reconstruction, Islamic learning technology development, enhancement of educators' epistemological competence, and institutional collaboration. This research contributes to contemporary Islamic education philosophy discourse by offering an integrative framework that produces holistic PAI learning to develop students with religious literacy, critical thinking abilities, spiritual awareness, and moderate character necessary for navigating the complexity of global society. Keywords: Islamic Epistemology, Kurikulum Merdeka, PAI Learning